KEBUTUHAN INDONESIA ATAS IMPLEMENTASI MODEL LAW ON ELECTRONIC SIGNATURES SEBAGAI UPAYA HARMONISASI HUKUM PERDAGANGAN INTERNASIONAL - Rahmat Darmaraga (2023)
The dynamics of technological developments in the trade sector have brought many conveniences, one of which is electronic signatures. This study focuses on how Indonesia needs to implement the Model Law on Electronic Signatures and the efforts that Indonesia can do in implementing the model law as an effort to harmonize international trade law. The research method used is normative juridical with a statutory approach and a comparative approach; primary materials in the form of legislation and international law models; Secondary materials are books, journals, and legal articles. The qualitative data that has been obtained were analyzed using descriptive writing techniques. The results of the research that have been carried out show that although they do not specifically regulate electronic signatures, several regulations in Indonesia have more or less implemented some of the provisions of the Model Law on Electronic Signatures. However, several regulatory revisions are still needed as well as legal certainty for international trade actors. The implementation is aimed at creating a harmonization of law in the field of international trade.